Nilai Budi Pekerti Dalam Garap Catur Lakon Pandawa Matirta Sajian Cahyo Kuntadi - Purnama, Putra Widhi; Harpawati, Tatik (Lakon Jurnal Pengkajian & Penciptaan Wayang, 2024)
Garap lakon (lakon treatment) Pandawa Matirta contains moral values. This study attempts to describe the moral values found in the shadow puppet performance Lakon Pandawa Matirta presented by Cahyo Kuntadi. Moral values can be seen from the garap lakon including janturan and ginem. This study uses the theory put forward by Zuriah. The research is qualitative with data collected through literature studies, interviews, and observations on social media. The results of the study indicate that there are moral values, namely (1) the relationship between humans and God including: knowing God as the creator, God as the giver (love, affection), God as the giver of rewards (good and bad), and worship as communication with God; (2) Moral values of human relationships with humans include: greeting when meeting, not making fun of someone beyond the limit, not being prejudiced, not offending their feelings, not slandering without evidence, always maintaining their good name, and helping someone in difficulties; (3) moral values related to human relations with the environment, namely caring for flora and fauna; and maintaining environmental cleanliness.